Ab‐initio molecular dynamics and hybrid explicit‐implicit solvation model for aqueous and nonaqueous solvents: GFP chromophore in water and methanol solution as case study. Issue 26 (8th August 2020) - Raucci, Umberto; Perrella, Fulvio; Donati, Greta; Zoppi, Maria; Petrone, Alessio; Rega, Nadia
Abstract: Solute–solvent interactions are proxies for understanding how the electronic density of a chromophore interacts with the environment in a more exhaustive way. The subtle balance between polarization, electrostatic, and non‐bonded interactions need to be accurately described to obtain good agreement between simulations and experiments. First principles approaches providing accurate configurational sampling through molecular dynamics may be a suitable choice to describe solvent effects on solute chemical–physical properties and spectroscopic features, such as optical absorption of dyes. In this context, accurate energy potentials, obtained by hybrid implicit/explicit solvation methods along with employing nonperiodic boundary conditions, are required to represent bulk solvent around a large solute–solvent cluster. In this work, a novel strategy to simulate methanol solutions is proposed combining ab initio molecular dynamics, a hybrid implicit/explicit flexible solvent model, nonperiodic boundary conditions, and time dependent density functional theory. As case study, the robustness of the proposed protocol has been gauged by investigating the microsolvation and electronic absorption of the anionic green fluorescent protein chromophore in methanol and aqueous solution. Satisfactory results are obtained, reproducing the microsolvation layout of the chromophore and, as a consequence, the experimental trends shown by the optical absorption in different solvents. Abstract : Accurate energy potentials, obtained by hybrid implicit/explicit solvation methods along with employing nonperiodic boundary conditions (non PBC), are required to represent bulk solvent around a large solute–solvent cluster. The protocol has been employed to investigate the microsolvation and electronic absorption of the anionic green fluorescent protein chromophore in solution.